Analyzes of Knowledge, Attitude, and Practice of Turkish Midwives and Puerperal Women Regarding Pharmacovigilance - Ergün, Yusuf; Toker, Eylem; Akben, Mine; Bekiroğlu Ergün, Tansel (Tropical Health and Medical Research, 2022)
Spontaneous reporting of adverse drug reactions (ADRs) is the backbone of the pharmacovigilance system. However, underreporting is still a fundamental hurdle around the globe that must be resolved. To analyze Turkish midwives' and puerperal women's knowledge, attitude, and practice regarding pharmacovigilance. A cross-sectional study on midwives (n=36) and puerperal women (n=227) was carried out from September 2019 to June 2020 in a State Hospital in Turkey. Data were collected by a questionnaire and analyzed by Mann-Whitney U, Kruskal-Wallis, and the Chi-Square tests. The knowledge level of midwives was significantly higher than that of the puerperal women. Although all midwives knew of adverse drug reactions, only half of the puerperal women had heard this. The awareness of the pharmacovigilance term was 97% and 2% in midwives and puerperal women, respectively. Similarly, 81% of the midwives were aware of the Turkish Pharmacovigilance Center (TPC), whereas only 1% of the puerperal women realized the fact. More than half of the midwives knew they could directly report ADRs to TPC. However, most did not know how they could send or report ADRs. Interestingly, only five midwives knew that congenital anomalies and congenital disabilities had been included in ADRs. Although the knowledge, attitude, and practice of Turkish midwives were significantly better than puerperal women regarding pharmacovigilance, it is apparent that both groups were insufficient to get involved in the pharmacovigilance system properly.